LITERATURE REVIEW: PAIN ASSESSMENT TOOLS IN CRITICALLY ILL ADULT PATIENTS WITH VENTILATOR - INDAH SRI WAHYUNINGSIH (NURSCOPE: Jurnal Penelitian dan Pemikiran Ilmiah Keperawatan, 2016)
Critically ill adult patients with a ventilator in intensive care often receive treatment that causes pain. Pain is a symptom that often occurs in critically ill adult patients with ventilator and it is very individual. Pain assessment in critically ill patients with the ventilator is needed because of the patient unable to self-report of pain. Pain assessments critically ill adult patients have been developed. However, there is no valid and reliable instrument to assess pain. The objectives of the literature review are to identify the instruments of pain assessment in patients with ventilator. The method of literature was performed through seeking publication of articles in MEDLINE, Google Search, PubMed, and Proquest with keywords pain assessment, tool, critical care, adult, critically ill, unconscious and ventilator. Literatures were undertaken from 2000-2015 with a cross-sectional study design, before and after studies and observational study. The results of the study according to the characteristics of the research was found five pain assessment instruments, they were NVPS, P.A.I.N, Comfort scale, BPS and CPOT. The validity and reliability CPOT is highest among others. All instruments had been measured its validity and reliability, but it had never tested its sensitivity and specificity. So, more researches should be conducted related to the sensitivity and specificity of all the instruments of pain in critically ill adult patients with a ventilator. Keywords : Pain assessment, critically ill, adult, ventilator.